Maize Growth Responses to a Humic Product in Iowa Production Fields: An Extensive Approach - Olk, Daniel C.; Dinnes, Dana L.; Callaway, Chad R. (Frontiers in Plant Science, 2022)
Field evaluations of commercial humic products have seldom involved replication across location or year. To evaluate the consistency of humic product efficacy in field conditions, we determined the effects of a humic product on maize (Zea mays L.) growth in high-yielding Midwestern (US) fields through the following two extensive approaches: (i) replicated strip plots in five site—year combinations from 2010 to 2013; and (ii) demonstration strips in 30–35 production fields annually from 2009 to 2011 that covered major areas of Iowa. Mechanized combine measurements of grain yield showed increases of 0.2–0.4 Mg ha–1 (1–4%) with humic product application for all five site—year combinations of the replicated strip plots. Six of 10 humic treatments within the fields responded positively (P < 0.07), and the positive responses of two more treatments approached significance at the benchmark of P = 0.10. In the demonstration strips, maize grain weight in hand-collected samples increased significantly (P < 0.004) with humic product application in each of the three growing seasons, and across all the three seasons by 6.5% (P < 0.001). Grain weight increased numerically for 76 of the 98 demonstration strips. Yield component analysis for both the replicated strip plots and the demonstration strips attributed the yield boosts largely to increased ear length, especially of the shorter ears. Humic product application caused significantly (P < 0.10) greater total leaf area in all eight field treatments at three site—year combinations. Humic product application did not consistently affect nutrient concentrations of the grain or stover or any measured soil property. These results represent among the widest geographic evaluations published on field efficacy of a humic product. They demonstrate the capability of a humic product to improve maize growth in high-yielding conditions.